The continuity of social identity among social researchers and its relationship to some demographic variables - Abbas , Nawar; Al -Daghaistani, Sanaa (Al-Adab Journal, 2026)
The current research aimed to measure the continuity of social identity among social researchers, according to the variables of gender and years of service, and the measure of the continuity of the social identity was prepared according to the theory of Fabio Sani (Fabio Sani, 2007) and is from (16) paragraph Disability and special needs and the Social Protection Authority), (Baghdad), and apply the scale to the statistical analysis sam (SPSS) for the purpose of extracting the results, the scale settled on (15) paragraphs in its final form, and they reached the following results: The research sample is highly level in the continuity of social identity, and that there is a statistically indicative difference in the continuity of social identity according to the gender variable and for the benefit of males, and that there is a statistically indicative difference in the variable of the service years and in favor of (10_19) and from (20 and more) at Its comparison with (1-9), and the researchers came out with a set of recommendations and proposals.